An Analysis of Second Semester English Department Students of UNP at Subject-Verb Agreement in their Paragraph Writing Assignments - Muhammad Wira Rizki; Don Narius; Witri Oktavia (Journal of English Language Teaching, 2019)
This research aimed to analyze the students’ subject-verb agreement accuracy in the paragraph writing assignments.  This research is descriptive quantitative research. The population in this research is the first year, second semester of 2018 English Department students of Universitas Negeri Padang. The sample was taken by using cluster random sampling. There are 40 students that become the sample of the research. In this research, the data was collected from the students and lecturers who taught paragraph writing class. Based on the findings and discussion about the students’ subject-verb agreement, the researcher found that Subject-Verb Agreement accuracy of second semester English Department students in Paragraph Writing course at Universitas Negeri Padang is 37,4%, which is categorized as Fail. The sequence of the types of errors from the highest to the lowest made by the students was omission, misformation, addition, and misordering.